Models for low-mass X-ray binaries in the elliptical galaxies NGC 3379 and NGC 4278: Comparison with observations - Fragos, T; Kalogera, V; Belczynski, K; Fabbiano, G; Kim, D; Brassington, N; Angelini, L; Davies, R; Gallagher, J; King, A; Pellegrini, S; Trinchieri, G; et al. (Institute of Physics Publishing, 2008)
We present theoretical models for the formation and evolution of populations of low-mass X-ray binaries (LMXBs) in the two elliptical galaxies NGC 3379 and NGC 4278. The models are calculated with the recently updated StarTrack code, assuming only a primordial galactic field LMXB population. StarTrack is an advanced population synthesis code that has been tested and calibrated using detailed binary star calculations and incorporates all the important physical processes of binary evolution. The simulations are targeted to modeling and understanding the origin of the X-ray luminosity functions (XLFs) of point sources in these galaxies. For the first time we explore the population XLF in luminosities below 1037 ergs s-1, as probed by the most recent observational results. We consider models for the formation and evolution of LMXBs in galactic fields with different CE efficiencies, stellar wind prescriptions, magnetic braking laws, and IMFs. We identify models that produce XLFs consistent with the observations both in shape and absolute normalization, suggesting that a primordial galactic field LMXB population can make a significant contribution to the total population of an elliptical galaxy. We also find that the treatment of the outburst luminosity of transient systems remains a crucial factor for the determination of the XLF, since the modeled populations are dominated by transient X-ray systems. © 2008. The American Astronomical Society. All rights reserved.